theorem obindeqS (F: set) (a: nat) {m: nat} (n: nat): $ obind n F = suc a <-> E. m (n = suc m /\ F @ m = suc a) $;
Step | Hyp | Ref | Expression |
---|---|---|---|
1 |
obind n F = suc a -> obind n F != 0 |
||
2 |
obind n F = 0 -> ~obind n F = 0 -> E. m (n = suc m /\ F @ m = suc a) |
||
3 |
conv ne |
obind n F = 0 -> obind n F != 0 -> E. m (n = suc m /\ F @ m = suc a) |
|
4 |
obind 0 F = 0 |
||
5 |
n = 0 -> obind n F = obind 0 F |
||
6 |
n = 0 -> obind n F = 0 |
||
7 |
n = 0 -> obind n F != 0 -> E. m (n = suc m /\ F @ m = suc a) |
||
8 |
n = 0 -> obind n F = suc a -> E. m (n = suc m /\ F @ m = suc a) |
||
9 |
n != 0 <-> E. m n = suc m |
||
10 |
conv ne |
~n = 0 <-> E. m n = suc m |
|
11 |
obind n F = suc a /\ n = suc m -> n = suc m |
||
12 |
obind (suc m) F = F @ m |
||
13 |
obind n F = suc a /\ n = suc m -> obind n F = obind (suc m) F |
||
14 |
obind n F = suc a /\ n = suc m -> obind n F = F @ m |
||
15 |
obind n F = suc a /\ n = suc m -> obind n F = suc a |
||
16 |
obind n F = suc a /\ n = suc m -> F @ m = suc a |
||
17 |
obind n F = suc a /\ n = suc m -> n = suc m /\ F @ m = suc a |
||
18 |
obind n F = suc a -> n = suc m -> n = suc m /\ F @ m = suc a |
||
19 |
obind n F = suc a -> E. m n = suc m -> E. m (n = suc m /\ F @ m = suc a) |
||
20 |
E. m n = suc m -> obind n F = suc a -> E. m (n = suc m /\ F @ m = suc a) |
||
21 |
~n = 0 -> obind n F = suc a -> E. m (n = suc m /\ F @ m = suc a) |
||
22 |
obind n F = suc a -> E. m (n = suc m /\ F @ m = suc a) |
||
23 |
n = suc m -> obind n F = obind (suc m) F |
||
24 |
n = suc m -> obind n F = F @ m |
||
25 |
n = suc m /\ F @ m = suc a -> obind n F = F @ m |
||
26 |
n = suc m /\ F @ m = suc a -> F @ m = suc a |
||
27 |
n = suc m /\ F @ m = suc a -> obind n F = suc a |
||
28 |
E. m (n = suc m /\ F @ m = suc a) -> obind n F = suc a |
||
29 |
obind n F = suc a <-> E. m (n = suc m /\ F @ m = suc a) |